2002
DOI: 10.22358/jafs/67816/2002
|View full text |Cite
|
Sign up to set email alerts
|

A note on the use of breadfruit meal (<i>Artocarpus incisus</i>) as a feed ingredient for broiler chickens

Abstract: Breadfruit meal (BFM) {Artocarpus incisus) was evaluated as a poultry feed ingredient in a pilot study. Diets containing 0, 25, 50 and 75 g BFM kg"1 were fed, ad libitum, to 240 day-old broiler chickens for a period of 8 weeks. Birds had free access to water. Performance criteria studied included feed intake, growth rate, efficiency of feed utilization, mortality, carcass and blood parameters. The concentration of BFM in the diet had significant negative influence on feed consumption (r =-0.96). Breadfruit mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 4 publications
(4 reference statements)
0
3
1
Order By: Relevance
“…The results of the current study on dressing percentage and internal organ weights are not in agreement with the findings of Ravindran and Sivakanesan (1995) and Atuahene et al (2002), who reported that these parameters were not affected by breadfruit treated diets. The enlargement of the liver and other internal organs could be attributed to the fact that the presence of anti-nutritive factors in the diet, in particular tannin and oxalate and increased detoxification in the body (Ologhobo et al, 2003;Adekunle et al, 2006;Qorbanpour et al, 2018).…”
Section: Parameter (%)contrasting
confidence: 98%
See 3 more Smart Citations
“…The results of the current study on dressing percentage and internal organ weights are not in agreement with the findings of Ravindran and Sivakanesan (1995) and Atuahene et al (2002), who reported that these parameters were not affected by breadfruit treated diets. The enlargement of the liver and other internal organs could be attributed to the fact that the presence of anti-nutritive factors in the diet, in particular tannin and oxalate and increased detoxification in the body (Ologhobo et al, 2003;Adekunle et al, 2006;Qorbanpour et al, 2018).…”
Section: Parameter (%)contrasting
confidence: 98%
“…Besides, Adekunle et al (2006) has revealed that higher growth and weight gain of broilers can be obtained by providing them with processed BFF compared to a corn-based diet. Processing of raw breadfruit is crucial because the presence of anti-nutritive factors in its raw form lowers the digestion, absorption, and utilization of energy, protein, and specific amino acids through the inhibition of digestive enzymes, thus resulting in poor growth and delayed maturity (Atuahene et al, 2002;Oladunjoye et al, 2010;Brea et al, 2013;Nikmaram et al, 2017).…”
Section: A-cmentioning
confidence: 99%
See 2 more Smart Citations